Acute Lysergic Acid Diethylamide Does Not Influence Reward-Driven Decision Making of C57BL/6 Mice in the Iowa Gambling Task - Elsilä, Lauri V.; Korhonen, Nuppu; Hyytiä, Petri; Korpi, Esa R. (Frontiers in Pharmacology, 2020)
While the interest towards psychedelic drugs in the fields of psychiatry and neuroscience has re-emerged during the last decades, the general understanding of the effects of these drugs especially, on the executive functions and goal-directed behaviors, remains deficient, both in humans and in commonly used animal models. Effects of acute doses of psychedelic lysergic acid diethylamide (LSD) on reward-driven decision-making were explored using the mouse version of Iowa Gambling Task. A total of 15 mice were trained to perform in a touch-screen adaptation of the rodent version of the Iowa Gambling Task, after which single acute doses of LSD (0.025, 0.1, 0.2, 0.4 mg/kg), serotonin 2A receptor-selective agonist 25CN-NBOH (1.5 mg/kg), d-amphetamine (2.0 mg/kg) and saline were administered immediately before the trial. 25CN-NBOH and the three lowest doses of LSD showed no statistically significant changes in the choice behavior nor in the general functioning during the gambling task trials. The highest dose, 0.4 mg/kg, of LSD significantly decreased the premature responding and increased the omission-percentage while having no effect on choice behavior in comparison to the saline control. Amphetamine significantly decreased the correct responses and premature responding while increasing the omission rate. As a conclusion, mice can perform previously learned, reward-driven decision-making tasks while under the acute influence of LSD at the commonly used dose-range.